EXPERIENCE OF COMBINED APPLICATION OF METHYLPREDNISOLONE ACEPONATE AND MOLETOLO COSMETICS STEROIDSANDVIAGRAJY IN THE TREATMENT OF DERMATOSES - Evgeny V. Orlov; Pavel E. Konnov; Antonina A. Arsenieva (State Scientific Center of Dermatovenereology and Cosmetology, 2018)
Skin diseases of non-infectious etiology, such as allergic contact dermatitis, atopic dermatitis, eczema  and chronic actinic dermatitis have a significant impact on the quality of patient's life, greatly reducing it. The most important place in the therapy of these diseases is found in topical glucocorticosteroids in combination with competent basic therapy.The aim of the study was to evaluate the clinical efficacy, safety profile, and tolerability of an external corticosteroid drug with a combination composition: methylprednisolone aceponate 0.1 % + urea 2 % (Komfoderm M2) in combination with dextpanthenol, allantoin and Shea butter (Dexpan plus cream) in dermatological practice in the treatment of eczematous process.Materials and methods. 48 patients, from 18 to 58 years old with mild to middle-severe eczematous process, were under observation, including 16 with allergic contact dermatitis, 14 patients with atopic dermatitis and 10 patients with eczema brushes, and 8 people with actinic dermatitis. Cream Komfoderm M2 was applied to the affected skin areas once a day in combination with cream Dexpan plus as standard therapy and emollient cosmetic. We investigated the parameters of the DLQI questionnaire "Dermatological Quality of Life Index" .Results As a result of the conducted observational study, data were obtained on the high effectiveness of therapy with the combined use of the drug Komfoderm M2 and Dexpan plus. An excellent evaluation of the efficacy of the scheme used was found in 37 (77 %) patients, a good one in 9 (18,8 %) and 2 (4.2 %) patients had a satisfactory result.Conclusions. This clinical study proves the high efficacy, safety and tolerability of the drugs - Cream with 0.1 % MPA and urea 2 % (Komfoderm M2) in combination with a cream containing dexpanthenol, allantonoin and Shea butter (Dexpan plus) in the treatment of eczematous process.